2015
DOI: 10.1116/1.4932533
|View full text |Cite
|
Sign up to set email alerts
|

Modification of porous SiOCH by first contact with water vapor after plasma process

Abstract: Porous low-k dielectrics used in integrated circuits interconnects are sensitive to plasma processes and exposure to moist ambient. In this paper, the authors use a vacuum and dry N2 sample transportation in conjunction with controlled atmosphere infrared spectroscopy (in transmission and in multiple internal reflections mode) to investigate the role of the first exposure to humidity on plasma-damaged porous low-k. They show that a porous low-k exposed to a N2/H2 or O2 plasma is irreversibly modified by the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Another serious problem during the PECVD plasma deposition process is plasma‐induced material damage. [ 16 ] Highly energetic plasma particles such as ions, electrons and photons bombarding continuously the surface of growing film which may cleavage Si‐C or Si‐O bonds and form Si‐H or Si‐OH moieties at broken bonds. The presence of Si‐H residues in SiOC films provides a leakage path for electrons and can produce films with poor electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Another serious problem during the PECVD plasma deposition process is plasma‐induced material damage. [ 16 ] Highly energetic plasma particles such as ions, electrons and photons bombarding continuously the surface of growing film which may cleavage Si‐C or Si‐O bonds and form Si‐H or Si‐OH moieties at broken bonds. The presence of Si‐H residues in SiOC films provides a leakage path for electrons and can produce films with poor electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum corresponding to the as-patterned sample exhibits the typical bonds and functional groups of a blanket silica-based low-k film. [9][10][11][12] The main absorption bands include the Si-O and Si-C bonds between ∼745-880 cm −1 , the asymmetric stretching band of Si-O-Si with a shoulder at the higher wavenumber side between 980-1250 cm −1 , the Si-CH 3 bond at 1275 cm −1 , and C-H bond at 2980 cm −1 . With the exception for the sample treated/cleaned with the formulated chemical, where the TiN hard mask was removed during the treatment (SEM shown in the next section), one notices that the baseline for all the other spectra drops off as the wavenumber increases.…”
Section: Resultsmentioning
confidence: 99%
“…3,4,8 Fourier transform infrared spectroscopy (FTIR) represents a method of choice for the characterization of blanket porous dielectrics. [9][10][11][12][13][14][15] The first objective of the study reported herein is to investigate the effect of moisture and aging on the evolution of the post-etch residues on a patterned, single damascene TiN HM/porous low-k dielectric structure for the case of without and with a reducing post-etch treatment. We will show that the presence -or not -of a layer of CFx-type residues at the surface significantly affects the degree of growth of the other type of residues, i.e.…”
mentioning
confidence: 99%